Mengkomunikasikan Matius 7:12 Sebagai Model Edukasi Moderasi Beragama di Kelurahan Matani Tiga, Kota Tomohon - Lempoy, Junaydi J.; Wakas, Jeremia Engelita; Manullang, Juanda (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study was to analyze the communication strategies implemented by the Matani Tiga sub-district community in Tomohon City in practicing the values ​​of religious moderation, and to describe how to communicate Matthew 7:12 as religious moderation education in the Matani Tiga sub-district in Tomohon City. Using the Lasswell communication model theory to analyze the five elements of communication, namely source, message, media, recipient and effect carried out by the Christian community in practicing religious moderation attitudes based on the principles of Matthew 7:12. The method used is descriptive qualitative using data collection techniques through observation, interviews, and documentation. The results of the study showed that the five elements of the communication process were carried out by the Christian community to achieve communication goals so that the effects given were in the form of changes in attitudes shown by the realization of harmonious and peaceful life as evidenced by the attitude of mutual respect and tolerance between the Christian and Muslim communities in the Matani Tiga sub-district in Tomohon City. Religious moderation implemented in the Matani Tiga sub-district in Tomohon City is through education. In formal education, the instillation of attitudes of religious moderation is supported in school learning through a creative, child-friendly approach that is connected to children's daily experiences. Non-formal education instilling values ​​of tolerance between religious communities is carried out through an adaptive approach at all age levels. Informal education also supports the formation of attitudes of religious moderation starting from the family environment by teaching attitudes of tolerance to children from an early age, and parents emulate these attitudes by helping communities of different religions.